Prevalence of Cyberbullying in the New Normal of Learning: Implications to Higher Education Institutions - Asio, John Mark R.; Dojello, Sherly DR.; Etrata-Filio, Rosalyn; Santos, Jackie Lyn M.; Capiral, Christine Ivy S.; Monzales, Rosalie P.; Patiam, Aljay Marc C.; Elpedes, Jefferson; Ambrosio, Aura Julia M. (Future Science / FSH-PH Publications, 2022)
In the advent of the “new normal” during the pandemic era, strategies to teach and learn switched to online. Students’ behavior and attitude also shifted from face-to-face to online. This study aims to assess the students' profiles and the prevalence of cyberbullying in the higher education institutions in Central Luzon, Philippines. The study used a descriptive-correlational technique with the help of an online survey to gather data. Using a convenience sampling technique, 300 higher education students participated in the online survey during the first semester of 2021–2022. In order to attain the objective of the study, the investigators used a standardized instrument. With the help of SPSS 23, the data analyst analyzed the gathered data using the following statistical tools: frequency, weighted mean, and non-parametrical tests like Kruskal-Wallis, Mann-Whitney U, and Spearman rho. The investigator found that the student-respondents were